PENGATURAN TINDAK PIDANA BAGI PELAKU PENIPUAN PHISING BERBASIS WEB - Faiz Emery Muhammad (Magister Hukum Universitas Semarang, 2023)
This study aims to analyze legal arrangements related to vague phishing in order to answer legal problems, namely whether it is in accordance with the elements of justice which is a legal ideal. The research discusses that the current criminal law rules need to be changed to pay attention to all parties (victims and the community) to be restored to their situation based on the ITE Law. This research method is a normative juridical using a statutory approach and a conceptual approach. The study yielded 2 points: first; That the current criminal law is still oriented towards the old penal system in accordance with the theory of criminal retaliation which is aimed at the punishment of the perpetrator and the rights of the victim are ignored. Second; There is no criminal arrangement regarding compensation that concretely regulates the crime of phishing. The novelty in this study is that it complements studies conducted in previous studies that only provide imprisonment for perpetrators as a form of compensation from the perpetrator and there is no personal responsibility from the perpetrator to return material losses suffered by the victim.